(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article presents a methodology for teaching descriptive geometry and computer graphics in an integrated manner, aimed at developing students’ spatial thinking, graphical reasoning, and skills in working within CAD environments. The study was conducted within the hydraulic engineering program at Andijan State Technical Institute, where the effectiveness of teaching through 3D modeling, theoretical-geometric analysis, and interactive visual environments was evaluated experimentally. The results of the experiment confirmed the high efficiency of the integrated methodology and scientifically substantiated the need to implement digital approaches in technical education.